Analisis Pengaruh Karakteristik dan Tata Kelola Perusahaan terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan di Indonesia - Kristina, Sonia; Wati, Erna (Global Financial Accounting Journal, 2019)
The purpose of this research is set out to investigate and discuss the influence of characteristics and corporate governance on social responsibility disclosures in Indonesian companies. Variables of the characteristics and corporate governance used in this research include government ownership, board of directors size, independent directors, company size, company age, liquidity, leverage and type of industry towards corporate social responsibility disclosure. The total sample which met the criteria consists of 443 companies that have been listed on the Indonesian Stock Exchange from the 2013-2017 period. Where is determined by purposive sampling method. The data used in this research are the annual reports and financial reports of all companies which are published through the IDX website. The data analysis method used is panel data regression. This research was processed using SPSS 25 and Eviews 10 programs. The results of this research showed that the variable profitability, company size and company age have a positive significant effect on corporate social responsibility disclosure. While the independent director's variables have a negative significant effect on corporate social responsibility disclosure. Moreover, the research confirmed that other variables such as liquidity, board of directors size, leverage, government ownership, and type of industry were not found to have a significant effect.